DESAIN SISTEM INFORMASI AKUNTANSI PERSEDIAAN OBAT BERBASIS KOMPUTER BERDASARKAN BATCH NUMBER DAN EXPIRED DATE - Andarwati, Mardiana (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2011)
Without the use of accounting information systems on data collection of medical supplies through the process of buying or selling drugs based on the batch number and expired date is takes more time in the service of payment transactions, because (a) they have to be calculated manually or with a calculator, (b) take time to monitor the inventory stock existing drugs (inventory check) because it is done manually, (c) take time in making the report, because employees have to reopen the existing data, so the work becomes less effective, (d) the possibility of data-data that is lost because not or forgot to record. Inventory of information system design based on computer-based drug batch number and expiration date using Accurate v.4 data collection will further help facilitate drug supply. Among other design inventory, purchasing credits, purchase order, debt repayment, cash sales, and inventory report based drug batch number and expired date. Â